2020
DOI: 10.3906/elk-1903-103
|View full text |Cite
|
Sign up to set email alerts
|

Performance optimisation of a sensing chamber using fluid dynamics simulation for electronic nose applications

Abstract: The sensor chamber plays a significant role in order to improve the performance of an electronic nose in terms of stability, repeatability, reproducibility, and sensitivity. Fluid dynamics simulations of six different configurations of 3D sensing chambers are presented to facilitate the efficient design of an electronic nose system comprising 64 sensor arrays. Numerical simulations were carried out to investigate the gas (zero air) flow behaviour inside these chambers under steady-state conditions for velociti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Another inspiration of nasal structure, for the construction of a bionic sensor chamber, was reported by Villarreal et al [ 26 ] and Chang et al [ 43 ], in which the effective transport of odor to sensors and exhalation of gas from the chamber was achieved. Dohare et al [ 44 ] reported a fluid dynamics simulation of cuboidal electronic nose sensor chambers with three different three-dimensional models with single and multiple inlets and outlets. Furthermore, they studied the influence of the introduction of four baffles directing the flow of the air in the chamber.…”
Section: Electronic Noses Sensor Chamber Designsmentioning
confidence: 99%
“…Another inspiration of nasal structure, for the construction of a bionic sensor chamber, was reported by Villarreal et al [ 26 ] and Chang et al [ 43 ], in which the effective transport of odor to sensors and exhalation of gas from the chamber was achieved. Dohare et al [ 44 ] reported a fluid dynamics simulation of cuboidal electronic nose sensor chambers with three different three-dimensional models with single and multiple inlets and outlets. Furthermore, they studied the influence of the introduction of four baffles directing the flow of the air in the chamber.…”
Section: Electronic Noses Sensor Chamber Designsmentioning
confidence: 99%
“…All the authors [27,94,[98][99][100][101][102][103][104][105][106][107] focusing on the sensors' chamber design agree that, inside the chamber, stable and uniform conditions should be reached as soon as possible. To ensure stable and uniform conditions, laminar flow is required in the chamber, with no stagnant or recirculating zones, which may result in a different exposure of the sensors to the target gas.…”
Section: Chamber Fluid Dynamicmentioning
confidence: 99%
“…To obtain a better and more reproducible response, the gas flow in the chamber should be laminar and as homogeneous as possible, meaning that all the sensors should be simultaneously exposed to the same gas flow [27,94,[98][99][100][101][102][103][104][105][106][107];…”
mentioning
confidence: 99%